Foodborne Illness Outbreak Investigation in a High-Profile Sports Club - Cavanagh, Kwendy (Sports Med Open, 2017)
A foodborne illness outbreak involving an elite sports team was investigated by a public health unit in Sydney, Australia. An epidemiological association was established between gastrointestinal illness and the consumption of food supplied by an external caterer, with a lamb meal most strongly associated with illness. Genetically identical Salmonella isolates were identified from clinical specimens, residual food items, and an environmental swab taken from the catering premises. The training schedule and other club operations were significantly affected by this outbreak. Increased susceptibility due to regular shared activities and the potential for significant impact upon performance indicates that sports clubs must ensure that food suppliers comply with the highest standards of hygiene. Collaboration with public health authorities assists in source identification and prevention of further transmission.